DO CAMPO À ARENA: A TRANSFORMAÇÃO DOS ESTÁDIOS DE FUTEBOL NA DINÂMICA URBANA DE PORTO ALEGRE - Eduardo Minossi de Oliveira; Janice Zarpellon Mazo; Paulo Roberto Rodrigues Soares (Universidade Estadual do Oeste do Paraná, 2013)
Brazil will be the host for another Football World Cup in 2014, as it ever was in 1950, and the city of Porto Alegre have a stadium as site of the competition again. Despite of the few kilometers separating the stadiums Beira-Rio and Eucaliptos, this period of time between the two World Cups, turned the role of football stadiums into global scale and specifically in the city of Porto Alegre. Understand the reasons that led the change of function of football stadiums in the city of Porto Alegre urban system is the objective of this work. The research indicates that stadiums were built while others went extinct, following the economic dynamics of the city and the capitalist interests of the real estate industry.